Analysis of the Legal Status of Children Born from Unregistered (Siri) Marriages under Law Number 16 of 2019 concerning Marriage at the Sorong Religious Court - Maria Juliana; Mariya Azis; Moh. Ery Kusmiadi (Equality Before The Law, 2026)
This study aims to comprehensively analyze the legal status of children born from unregistered (siri) marriages under the framework of Law Number 16 of 2019 concerning Marriage and its judicial implementation at the Sorong Religious Court. Using an empirical legal research method with a socio-legal approach, data were collected through in-depth interviews with judges, registrars, and advocates at the Sorong Religious Court, as well as document analysis of case files concerning applications for marriage ratification (isbat nikah). The results show that, according to the judges of the Sorong Religious Court, the regulation of the legal status of children from siri marriages already has an adequate legal basis through Law Number 16 of 2019, the Compilation of Islamic Law, the Child Protection Law, and Constitutional Court Decision Number 46/PUU-VIII/2010. In practice, children from siri marriages can still obtain legal certainty of status through the mechanism of marriage ratification followed by a determination of the child's parentage. However, the interview results indicate that the main obstacles do not lie in the juridical aspect, but rather in the low level of public knowledge regarding legal procedures, the strong cultural influence that still regards siri marriage as a normal practice, limited public access to judicial services in island regions, and economic factors that cause communities to delay marriage registration. Pregnancy outside of marriage and early-age marriage are also factors that encourage the occurrence of siri marriages and affect the fulfillment of children's civil rights. Legal protection for children from siri marriages is, in principle, already available through the applicable legal mechanisms; however, its effectiveness remains influenced by social, cultural, and economic factors, as well as low public legal awareness. Therefore, enhanced legal outreach, easier access to judicial services, and education on the importance of marriage registration are needed to ensure optimal protection of children's rights.